The effect of menstrual cycle on inter-joint coordination variability during roundhouse kicks in taekwondo - Samira Sadat Sajjadi; Ali Abbasi; Zeynab Hadavi; Mehdi Khaleghi Tazji; Zdenek Svoboda (BMC Women's Health)
Abstract Background This study aimed to investigate the effect of the menstrual cycle on the coordination variability of the lower-limb joints during the taekwondo roundhouse kick in professional athletes. Methods Twenty professional taekwondo female athletes voluntarily participated in the study. The participants visited a laboratory thrice during their menstrual cycles’ follicular, ovulation, and luteal phases. The lower-extremity kinematic data were collected during the roundhouse kick. Range of motion (ROM) and coordination variability of the lower-extremity joints in sagittal plane were calculated and compared for different menstrual cycles. Findings The results did not show significant differences in the ROM of the joints for the different menstrual cycles. Moreover, the results of a vector analysis using the repeated measures ANOVA did not show significant differences in joint coordination patterns and variability for different menstrual cycles. However, there were fluctuations in the coordination variability during the ovulation phase in the hip–ankle coupling, but this was not statistically significant. Interpretation The results suggest that female taekwondo players must be cautious of training during the ovulation phases of their menstrual cycles. However, more research is needed to better understand the effect of menstrual cycle on the coordination patterns of joints and segments.